2009
DOI: 10.4049/jimmunol.0803032
|View full text |Cite
|
Sign up to set email alerts
|

Superantigen- and TLR-Dependent Activation of Tonsillar B Cells after Receptor-Mediated Endocytosis

Abstract: Classical B lymphocyte activation is dependent on BCR cross-linking in combination with physical interaction with Th cells. Other B cell molecules that contribute to the activation are complement, cytokine, and TLRs recognizing specific pathogen-associated molecular patterns. Moraxella (Branhamella) catarrhalis is a common Gram-negative respiratory pathogen that induces proliferation in human IgD-expressing B cells independently of T cell help. The activation is initiated by the B cell superantigen Moraxella I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 55 publications
1
37
0
Order By: Relevance
“…catarrhalis can be found adjacent to B cells in tonsils [6] and we have recently shown that this pathogen is internalized by tonsillar B cells [13]. Intracellular survival of bacteria in B cells would thus be a potential escape mechanism in the host.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…catarrhalis can be found adjacent to B cells in tonsils [6] and we have recently shown that this pathogen is internalized by tonsillar B cells [13]. Intracellular survival of bacteria in B cells would thus be a potential escape mechanism in the host.…”
Section: Resultsmentioning
confidence: 98%
“…catarrhalis would theoretically also contain MID as vesicles basically comprise outer membrane components, i.e., LPS, phospholipids and outer membrane proteins. The potential of OMV to carry and long-distance deliver diverse virulence factors prompted us to hypothesize that Moraxella OMV can activate human B cells as has been proven with whole bacteria [13],[14]. The initial step in B cell activation requires M .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their existence has been reported in some respiratory Gram-negative bacteria. Examples include protein D from Haemophilusinfluenzae [19] and Moraxella IgD-binding protein from Moraxella catarrhalis [20], both of which bind human IgD with high affinity. Thus, it is reasonable to believe that mast cells recognize the invasion of some Gram-negative bacteria through sensing their immunoglobulin-binding proteins in antigenindependent manners.…”
Section: Indirect Recognitionmentioning
confidence: 99%
“…However, in light of the finding that many human IgM 2 /IgD + plasmablasts express IgD with hypermutated VH (35) and VL (39) regions that are predicted to be incapable of binding Ag, combined with the fact that secreted IgD made by stimulated IgM 2 /IgD + plasmablasts binds to Moraxella catarrhalis and Haemophilus influenzae type a and type b (40), it is plausible that catfish secreted IgD, which was shown to be expressed in serum (22), functions through its Fc portion. For example, the IgDbinding proteins of M. catarrhalis and H. influenzae were shown to be stimulatory for human IgM 2 /IgD + B cells and bind human IgD via the Cd1 domain (68)(69)(70)(71)(72), Furthermore, in a recent study, it was demonstrated that IgD cross-linking by the superantigen M. catarrhalis IgD-binding protein leads to IgD-mediated endocytosis and B cell proliferation, because the engulfed bacteria activate various TLRs (mainly TLR 9) (73). Therefore, it is feasible that catfish IgM 2 /IgD + B cells, or even a certain subset of IgM + / IgD + B cells, could become activated by an "unidentified" pathogen, which has developed IgD-binding properties.…”
Section: /Igdmentioning
confidence: 99%